Rethinking financial sustainability for cultural and creative industries in the AI age: a theoretical model - Dombou, Dany; Jekinnou, Christian; Bassy, Blick (BOHR International Journal of Finance and Market Research, 2025)
Acknowledging that the Cultural and Creative Industries (CCIs) face enormous difficulties such as lack of physical substances for assets, volatile demand, and fragmented financing mechanisms, it is important to note that they have a central role in the global economy as they promote innovation, employment, and cultural diversity. The artificial intelligence (AI) upswing and digitalization modify value chains in a great way by disrupting traditional creative processes, revenue models, and regulatory frameworks. This paper aims at developing a theoretical model for financial sustainability as far as CCIs are concerned by integrating five key dimensions: (i) financial strength, (ii) digitalization, (iii) AI integration, (iv) governance quality, and (v) market adaptability. Our multiplicative resilience function demonstrates that deficiencies in any of these dimensions significantly increase sectoral fragility, reinforcing the need for a balanced and holistic approach. Using a systematic review of 53 academic and institutional sources, we identify emerging financial strategies—such as hybrid public-private financing, crowdfunding, and blockchain-based models—and assess their potential in mitigating CCIs’ economic vulnerabilities. Our findings highlight that AI-driven transformation can be an asset or a liability, depending on the strength of governance frameworks regulating intellectual property rights, platform monopolization, and ethical AI adoption. The proposed model provides a diagnostic and strategic tool for policymakers, investors, and industry stakeholders, offering a framework to enhance CCIs’ resilience in an era of rapid technological evolution.